Insights into the role of Nrf2 in vitiligo pathogenesis: a target for herbal medicine - Qawasmeh, Abdel; Qaisiya, Mohammad; Ishnaiwer, Areej; Khdour, Dana; Shawar, Shoroq; Fallah, Seema; Hashlamon, Duha; Sinokrot, Hanadi; Kharaiwesh, Alaa (Frontiers in Natural Products, 2025)
Vitiligo (skin depigmentation) affects approximately 2% of the global population. It is characterized by a decrease in the number of pigment-forming cells known as melanocytes in the skin. Vitiligo is classified according to its extent and distribution into segmental (affecting one side of the body) and non-segmental (affecting both sides of the body). Vitiligo is an autoimmune disease characterized by complex and multifactorial genetic and non-genetic factors. The genetic factors are related to gene defects on HLA regions that code the histocompatibility complex, creating autoimmune response. Non-genetic factors include the exposure of melanocytes to oxidative stress and environmental factors. Conventional therapies include corticosteroids, immunomodulators, vitamins, phototherapy, surgery, and laser therapy. The use of complementary medicines such as plants, their extracts, and natural compounds in managing vitiligo has consistently been shown in many studies to be effective in the management and treatment of vitiligo. This review summarizes the most recent advances in understanding the pathogenesis of vitiligo, with an emphasis on the role of the Nrf2 pathway machinery and the effectiveness of herbal medicines and their extracts in vitiligo management and treatment. Plants such as Ginkgo biloba, Olea europaea, Cucumis melo, Camellia sinensis, and Allium sativum exhibit activity against vitiligo. The possible mechanisms by which these plants act are summarized in this review.